2000
DOI: 10.1034/j.1600-0676.2000.020003257.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of hepatitis C genome in semen of infected men by polymerase chain reaction, branched DNA and in situ hybridization

Abstract: Our results confirmed the lack of detection of HCV RNA in semen by PCR- and non-PCR-dependent techniques and support the view that viral contamination in semen remains, if present, at a very low level. Nevertheless, epidemiological studies are required to definitively assess the absence of sexual transmission of HCV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…The management of HCV-infected men enrolled in programs of medically assisted reproduction is highly dependent upon the definition of standardized protocols of detection of HCV RNA in semen. Actually, although previous studies have reported the presence of HCV RNA in seminal plasma of men chronically infected with HCV and coinfected (7,10,15) or not coinfected (12,13) with human immunodeficiency virus (HIV), other investigators have found the opposite pattern (6,8,16). Those contradictory results could be explained, at least in part, by the heterogeneity of the populations studied and by the diversity and the poor standardization of the techniques used for the extraction of RNA from semen and for the reverse transcription (RT)-PCR protocols.…”
mentioning
confidence: 73%
“…The management of HCV-infected men enrolled in programs of medically assisted reproduction is highly dependent upon the definition of standardized protocols of detection of HCV RNA in semen. Actually, although previous studies have reported the presence of HCV RNA in seminal plasma of men chronically infected with HCV and coinfected (7,10,15) or not coinfected (12,13) with human immunodeficiency virus (HIV), other investigators have found the opposite pattern (6,8,16). Those contradictory results could be explained, at least in part, by the heterogeneity of the populations studied and by the diversity and the poor standardization of the techniques used for the extraction of RNA from semen and for the reverse transcription (RT)-PCR protocols.…”
mentioning
confidence: 73%
“…Yet, among individuals infected by HCV, approximately 40% have no history of blood transfusion or intravenous drug use [2,3]. The role of sexual transmission in the spread of HCV infection has been a matter of debate for several years, with many studies suggesting its relevance [4][5][6][7][8][9][10][11][12], while other authors continue to discount it [13][14][15]. Co-infection with HCV is common in subjects infected with HIV [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus IVF is not contraindicated in these couples (15,16). Moreover, the value of routine detection of HCV viral RNA in seminal fluid and culture medium is questionable (17), and the results must be interpreted with caution, as seminal amplification inhibitors may render the results of PCR unreliable (11,18). Notwithstanding the possibility of sexual transmission, a recent report has drawn attention to the possibility of nosocomial transmission of HCV during ancillary procedures for ART (19), indicating the need for exercising special precaution in specimen handing in the embryology laboratory.…”
Section: Introductionmentioning
confidence: 99%